RF Probe-Induced On-Wafer Measurement Errors in the Millimeter-Wave Frequency Range - Müller, Daniel (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2018)
Measurement at millimeter-wave frequencies are prone to parasitic effects which distort the overall results. Especially the use of RF probes introduces unknown distortions, even after the measurement setup is calibrated. This works investigates these distortions based on electromagnetic field simulations of integrated circuits in conjunction with models of the used RF probes. This allows to comprehend the observed distortions and successfully resolve the root of the distortions.